A Calderón‐preconditioned single source combined field integral equation for analysis of bi‐isotropic object. (26th November 2014) - Shi, Yan; Tian, Cheng‐Yi; Liang, Chang‐Hong
Abstract In this paper, a Calderón‐preconditoned single source combined field integral equation (SSCFIE) has been developed to analyze electromagnetic scattering from bi‐isotropic objects. The field decomposition method is adopted to split the homogeneous bi‐isotropic media into two uncoupled isotropic media instead of direct calculation of complicated Green's function in bi‐isotropic material. Unlike dual source integral equation, the Calderón‐preconditioned single source electric and magnetic integral equations in the presence of bi‐isotropic media are constructed and combined to make the proposed algorithm free from dense mesh breakdown and spurious resonance. Numerical results show good performance of the proposed algorithm. Copyright © 2014 John Wiley & Sons, Ltd.